PERUBAHAN PENUTUP LAHAN DAN PENGGUNAAN LAHAN KAWASAN HUTAN LINDUNG MENJADI LAHAN AGROFORESTRY MENGGUNAKAN METODE INDEKS VEGETASI KECAMATAN PANTI, KABUPATEN PASAMAN - Septia Devi; Triyatno Triyatno (JURUSAN GEOGRAFI FIS UNP, 2020)
This research aims to: 1) determine the extent of land cover change in protected forest areas in Panti District, Pasaman Regency in 2015, 2016, 2017, 2018 and 2019. 2) Know the types of agroforestry plants in protected forest areas in Panti District, Pasaman Regency.This type of research is quantitative with a spatial approach using the NDVI (Normalized Difference Vegetation Index) technique and field accuracy test to see changes in the area of protected forest cover in the Panti District of Pasaman Regency based on its vegetation density. The results of the research are: 1) changes in land cover of protected forest areas to agroforestry land using vegetation index techniques resulted in changes in the area of ​​protected forest area in 2015 covering an area of ​​131.176,44 Ha or 84% in 2016 remaining 109.287,47 Ha or 82% in 2017 remaining 83.230,47 Ha or 76% of 2018 left 57.155,94 Ha or 67% and in 2019 there were 34.284,51 Ha or 60%.This proves that there is a reduction in the area of ​​protected forest. 2) The result of the ground check showed that the types of agroforestry plants in protected forest areas were dry land agricultural crops including cacao (Theobroma cacao), rubber (Hevea brasiliensis), arabica coffea (Coffea arabica) and robusta coffea (Coffea canephora).